2010
DOI: 10.3109/13685538.2010.487553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and risk factors of testosterone deficiency in a population-based cohort of men: results from the study of health in Pomerania

Abstract: Besides aging alone, lifestyle and different comorbidities were associated with TT level decline, suggesting that the age-related TT decline may be at least partly prevented through the management of potentially modifiable risk factors and health related behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 49 publications
6
63
1
5
Order By: Relevance
“…The decline in FT with age is exaggerated by the concurrent rise in SHBG. The magnitude of the observed change in testosterone (K0.1 nmol/l per year) was modest and similar to that in previous longitudinal studies (3,14,30,32).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The decline in FT with age is exaggerated by the concurrent rise in SHBG. The magnitude of the observed change in testosterone (K0.1 nmol/l per year) was modest and similar to that in previous longitudinal studies (3,14,30,32).…”
Section: Discussionsupporting
confidence: 67%
“…More recently, longitudinal studies have also confirmed that these findings have fuelled a substantial worldwide increase in testosterone prescription (10,11,12,13). Testosterone decline may not be an inevitable part of ageing, being related to adverse health and lifestyle factors, such as obesity; it may, therefore, be potentially preventable and reversible (5,6,7,14).…”
Section: Introductionmentioning
confidence: 99%
“…In prospective studies, the metabolic syndrome predicts low testosterone (Laaksonen et al 2005). Several large prospective studies have shown that weight gain or development of type 2 diabetes is major drivers of the age-related decline in testosterone levels (Travison et al 2007, Haring et al 2010. Indeed, there is increasing evidence that healthy ageing by itself is generally not associated with marked reductions in testosterone (Sartorius et al 2012).…”
Section: Evidence That Low Testosterone Is a Consequence Of Dysglycaementioning
confidence: 99%
“…This is supported by observational studies showing that weight gain and development of diabetes accelerate the age-related decline in testosterone. This suggests that this decline may be decelerated through management of health and lifestyle factors (Travison et al 2007, Haring et al 2010.…”
Section: Testosterone and Insulin Resistance: A Bilateral Relationshipmentioning
confidence: 99%
“…Based on the findings from various prospective epidemiological studies (Morley et al 1997, Zmuda et al 1997, Harman et al 2001, Feldman et al 2002, Haring et al 2010, it is now well established that total testosterone (TT) concentration shows an age-related decline, with mean serum TT concentration at the age of 75 years being approximately two-thirds of that at age 25 years (Vermeulen et al 1996). Over and above this established age-related decline at the population level, a considerably larger inter-individual variability of TT concentrations can be observed at any age.…”
Section: Journal Of Endocrinology (2012) 215 3-16mentioning
confidence: 99%